Agents of Apocalypse : Epidemic Disease in the Colonial Philippines - De Bevoise, Ken, 1943- (Book collections on Project MUSE., 2001)
As waves of epidemic disease swept the Philippines in the late nineteenth century, some colonial physicians began to fear that the indigenous population would be wiped out. Many Filipinos interpreted the contagions as a harbinger of the Biblical Apocalypse. Though the direct forebodings went unfulfilled, Philippine morbidity and mortality rates were the world's highest during the period 1883-1903. In Agents of Apocalypse, Ken De Bevoise shows that those "mourning years" resulted from a conjunction of demographic, economic, technological, cultural, and political processes that had been building.